BRAF mutation in colorectal cancer: an update - Colombo, Alfredo; Porretto, Concetta Maria; Rosati, Gerardo (Archive of Oncology, 2022)
Colon cancer is a leading cause of cancer-related deaths worldwide. About 10% of all colon cancer patients are found to have a mutation in BRAF proto-oncogene that arise as a result of a substitution of amino acid valine with glutamate at position 600 (V600E). This specific mutation is also found in melanomas, but at even higher percent – in up to 60% of patients. A particular category of drugs called BRAF inhibitors, have been developed in order to increase survival. But, while in patients with melanoma this class of drugs work well especially when combined with mitogen-activated protein kinase inhibitors, they have low efficacy in patients with metastatic colorectal cancer suggesting different mechanism of action and development of drug resistance. This review summarise recent findings aimed to highlight events in BRAF mutations in metastatic colorectal cancer.